FAKTOR-FAKTOR YANG MEMPENGARUHI KESADARAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KAB SUKOHARJO (Lembaga Pengembangan Kinerja Dosen, 2022)
In this study, the impact of the following factors will be assessed: (1) taxpayer awareness of motor vehicle taxpayer compliance in Sukoharjo regency; (2) Tax sanctions on motor vehicle taxpayer compliance in Sukoharjo regency; (3) taxation socialization of motor vehicle taxpayer compliance in Sukoharjo regency; and (4) taxpayer service quality on motor vehicle taxpayer compliance in Sukoharjo regency. 541,604 people made up the study population, and 100 taxpayers made up the sample. Data collection techniques through surveys and to analyze data using validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity Test), T test, F test, and R Test. Significance value of 0.25 obtained from the analysis of the T test indicates that the taxpayer awareness variables significantly affect taxpayer compliance. Significance score of 0.04 indicates that the variable tax sanctions have a considerable impact on taxpayer compliance. Significance score of 1,000 indicates that the tax socialization variable has no significant effect on taxpayer compliance. Significance value of 0.046 indicates that the quality of tax services that vary significantly affect taxpayer compliance.